Pemahaman Akuntansi Zakat Dalam Meningkatkan Transparansi dan Akuntabilitas pada Badan Amil Zakat Palembang - Fitriasuri Fitriasuri; Ade Kemala Jaya (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
Muslim population in Indonesia has encouraged the implementation of Islamic law in social and economic life for example zakat. Badan Amil Zakat as an institution engaged in the management of zakat still needs to improve its performance so that the optimization can be achieved. Indonesian Institute of Accountants (IAI) has issued a standardization of zakat accounting under SFAS 109. This study aims to determine how an understanding of accounting concepts in Amil Zakat charity in Palembang with a case study approach and qualitative analysis techniques. The results showed that the understanding of accounting zakat is still low but about its benefits are pretty good. IAI existence has been known to the public, but the standard is not yet widely known. Zakat only be understood as a liability in accordance with the guidelines of Islamic law, has not been conceived as a public activity that requires accountability.